Clinical, Radiographic, and Molecular Analysis of Patients with X-Linked Hypophosphatemic Rickets: Looking for Phenotype–Genotype Correlation - Marco A. Olivas-Valdez; Armando Blanco-López; Daniela Velázquez-Arestegui; Teresita Vera-Zazueta; Douglas Colmenares-Bonilla; Lilian Reyes-Morales; Miguel A. Blanco-Uriarte; Lucero Monterde-Cruz; Alberto Hidalgo-Bravo (Diagnostics)
Background/Objectives: X-linked hypophosphataemic rickets (XLH) represents the most frequent type of rickets from genetic origin, it is caused by mutations on the PHEX gene. The main clinical manifestations are short stature and bone deformities. Phenotype variation is observed at the intrafamily and interfamily level. The bases for this variation are not fully understood. The aim of this study was to investigate if there is a phenotype–genotype correlation in a cohort of patients with confirmed diagnosis of XLH. Methods: We recruited a total of 130 patients of Mexican Mestizo origin with confirmed molecular diagnosis of XLH; this is one of the largest cohorts reported. Results: Radiographies for calculating the rickets severity score (RSS) were available from 50 patients. A total of 56 different pathogenic variants were found among the study population; from them, 31 variants have not been previously reported. We compared the RSS values between individuals considering clinical and biochemical characteristics such as age, height, sex, phosphorus, and alkaline phosphatase in serum; no significant differences were observed. Then, we compared the RSS considering if the variant was intronic or exonic and considering the presence of a truncated protein or not. None of the two comparisons showed significant differences. Conclusions: We did not find a genotype–phenotype correlation in the study population. Despite the knowledge regarding the genetic cause of XLH, the mechanisms driving the intrafamily and interfamily variability remain elusive. More analyses looking for the genotype–phenotype correlation are necessary in other populations, especially considering the discovery of new mutations in patients from different origin.